EVALUASI KETERGUNAAN WEBSITE PERPUSTAKAAN UNIVERSITAS INDONESIA MENGGUNAKAN SYSTEM USABILITY SCALE - Lazuardi Nuriman, Muhammad; Mayesti, Nina (BACA: Jurnal Dokumentasi dan Informasi, 2020)
The University of Indonesia (UI) Library has a website that is accessed by students to meet their information needs. Evaluation of usability on the university library website is important so that users remain loyal to visit it and the results can be used as a basis for further development. This study aims to evaluate the usability on the University Indonesia Library website between the batch of 2016 and 2019 and compare its results. The method used in this study is descriptive quantitative using a questionnaire based on the System Usability Scale. Questionnaires are distributed online through instant messaging applications and social media. The research data were analyzed using the System Usability Scale score calculation technique, then the results were compared between the two batches. The results of the analysis showed that the batch of 2016 had a better website usability value than the batch of 2019. The two batches also have good user experience based on the five components of Nielsen's usability, namely learnability, efficiency, memorability, errors, and satisfaction. The usability of the Indonesian Library's website has not been well accepted by students of batch 2016 and 2019, although there are differences in scores between the two batches. Because the SUS score is below average and below acceptable, further research can be conducted using different method or instrument to identify the existing problems.